IMMISCIBILITY BETWEEN SILICATE MAGMAS AND AQUEOUS FLUIDS: A MELT INCLUSION PURSUIT INTO THE MAGMATIC-HYDROTHERMAL TRANSITION IN THE OMSUKCHAN GRANITE (NE RUSSIA) - Kamenetsky V.S.; Davidson P.; Naumov V.B.; van Achterbergh E.; Ryan C.G. (My University, 2004)
Exsolution (unmixing) of the volatile element-rich phases from cooling and crystallising silicate magmas is critical for element transport from the Earth’s interior into the atmosphere, hydrosphere, crustal hydrothermal systems, and the formation of orthomagmatic ore deposits. Unmixing is an inherently fugitive phenomenon and melt inclusions (droplets of melt trapped by minerals) provide robust evidence of this process. In this study, melt inclusions in phenocrystic and miarolitic quartz were studied to better understand immiscibility in the final stages of cooling of, and volatile exsolution from, granitic magmas, using the tin-bearing Omsukchan Granite (NE Russia) as an example.Primary magmatic inclusions in quartz phenocrysts demonstrate the coexistence of silicate melt and magma-derived Cl-rich fluids (brine and vapour), and emulsions of these, during crystallisation of the granite magma. Microthermometric experiments, in conjunction with PIXE and other analytical techniques, disclose extreme heterogeneity in the composition of the non-silicate phases, even in fluid globules within the same silicate melt inclusion. We suggest that the observed variability is a consequence of strong chemical heterogeneity in the residual silicate-melt/brine/vapour system on a local scale, owing to crystallisation, immiscibility and failure of individual phases to re-equilibrate. The possible evolution of non-silicate volatile magmatic phases into more typical “hydrothermal” chloride solutions was examined using inclusions in quartz from associated miarolitic cavities.